2011
DOI: 10.1088/0964-1726/20/12/124007
|View full text |Cite
|
Sign up to set email alerts
|

Formation of motile assembly of microtubules driven by kinesins

Abstract: Microtubule (MT) and kinesin are rail and motor proteins that are involved in various moving events of eukaryotic cells in natural systems. In vitro, the sliding motion of microtubules (rail) can be reproduced on a kinesin (motor protein)-coated surface coupled with adenosine triphosphate (ATP) hydrolysis, which is called a "motility assay". Based on this technique, a method was recently established to form MT assemblies by an active self-organization (AcSA) process, in which MTs are crosslinked during a slidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
2
3
0
Order By: Relevance
“…In order to develop a robustly controlled molecular swarm system, we systematically investigated the effect of related physicochemical parameters on the DNA assisted swarming of a self-propelled biomolecular motor system, MT-kinesin. We found that the effects are comparable to those discovered in previous studies where self-assembly of MTs was regulated using streptavidin (St)-biotin (Bt) crosslinkers system 32 34 . Unlike the self-assembly of MTs using the strong St-Bt interaction, where MTs assembled even when they moved in opposite direction 32 , 33 , almost no sticking of MT swarms on the kinesin-coated surface was noticed in the present system.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In order to develop a robustly controlled molecular swarm system, we systematically investigated the effect of related physicochemical parameters on the DNA assisted swarming of a self-propelled biomolecular motor system, MT-kinesin. We found that the effects are comparable to those discovered in previous studies where self-assembly of MTs was regulated using streptavidin (St)-biotin (Bt) crosslinkers system 32 34 . Unlike the self-assembly of MTs using the strong St-Bt interaction, where MTs assembled even when they moved in opposite direction 32 , 33 , almost no sticking of MT swarms on the kinesin-coated surface was noticed in the present system.…”
Section: Discussionsupporting
confidence: 87%
“…We found that the effects are comparable to those discovered in previous studies where self-assembly of MTs was regulated using streptavidin (St)-biotin (Bt) crosslinkers system 32 34 . Unlike the self-assembly of MTs using the strong St-Bt interaction, where MTs assembled even when they moved in opposite direction 32 , 33 , almost no sticking of MT swarms on the kinesin-coated surface was noticed in the present system. This observation suggests that swarming of MTs was favored by moderate interaction between l -DNA and r -DNAs attached to MTs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Alongside programming with DNA interaction, different physicochemical parameters of biomolecular motors, DNA, and the surrounding environment can play important roles to control the swarming of MTs, which is required for making sustainable molecular swarm robot systems (Keya et al 2018a). The DNA-based interaction is moderate in strength and specifically controls the interaction between MTs moving in the same direction, unlike the strong streptavidinbiotin crosslinker system, where MTs bind even moving in the opposite direction and results in sticking of MT swarms (Kawamura et al 2011). The binding affinity of DNAconjugated MTs promoting the swarm formation depends on the direction of motion and collision between MTs.…”
Section: Control Of Swarming Of Dna-programmed Biomolecular Enginesmentioning
confidence: 99%
“…An example procedure for the motility assay after obtaining the materials of RMT and frozen kinesin-GFP is described below. 16) A pair of coverslips with a pair strip of double sided-sticky tape (spacer) is used as an observation container for assembling a flow-cell (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%